Christos Yannaras’s Conception of State, Society and Politics and the Greek Apophatic Tradition - Gligorić, Miroljub (Interdisciplinary journal for religion and transformation in contemporary society, 2021)
Abstract The article demonstrates a concept of state, society and politics coined by contemporary Greek religious philosopher Christos Yannaras. The concept derives from two sources: on the one hand from the criticism of the modern cataphatic forms of state and society and on the other hand from the apophatic character of the Greek polis. With this creative critical synthesis, based on the apophatic attitude, Yannaras produces a conception of a new polity, contributing to the liberation of the human subject from various aspects of alienation in the cataphatic systems.